IoT Enabled IV Pole with Integrated Patient Healthcare Monitoring System - Pandit, Vaibhav; Patil, Bhavesh; Pardeshi, Siddharthsing; Dahale, Prashant (International Journal of Research in Interdisciplinary Studies, 2025)
Intravenous (IV) therapy is a common and effective treatment method in medical settings, crucial for administering medications and fluids directly into a patient's bloodstream. However, traditional monitoring of IV saline bags and patient health is prone to human error, leading to risks such as air embolism or incorrect fluid administration. The project aims to develop a "Smart IV Pole" system using IoT technologies to monitor saline levels during intravenous (IV) therapy. The system integrates an ESP32 microcontroller, load cell, temperature sensor, SPo2 sensor, and LCD display. It automates the monitoring of saline weight and provides a warning when the saline level becomes critically low. An IoT-enabled IV pole with an integrated patient healthcare monitoring system is a smart medical device designed to enhance patient care in hospitals. The IV pole is equipped with sensors and connected to the Internet of Things (IoT) to monitor various patient health parameters, such as heart rate, blood pressure, oxygen levels, and IV fluid levels. This data is transmitted in real-time to healthcare providers, allowing for continuous monitoring and timely interventions.